Differential behavior of the summer cover crops in the absorption and translocation of copper - Vendruscolo,Diogo (2018)
ABSTRACT: Phytoremediation is an alternative technique used to treat copper-contaminated soils. The objective of this research was to explore the behavior of nine summer cover crops regarding the growth, absorption and translocation of copper in soils with contamination levels exceeding the Value of Prevention, with a view to selecting plants for phytoremediation programs. In the experiments the Cambisol was contaminated with copper, added in doses of 0, 100, 200, 400, 500 and 600mg kg-1, in which the following nine plants were cultivated under greenhouse conditions: Canavalia ensiformis, Cajanus cajan, Dolichos lablad, Mucuna cinereum, Mucuna aterrima, Crotalaria juncea, Crotalaria spectabilis, Pennisetum glaucum and Paspalum notatum. At 90 days after sowing the plants were evaluated for dry mass of shoot and root, Cu, N, P, K, Ca, Zn, and Fe levels in the shoot and Cu in the roots. High soil Cu levels induced a decline in the phosphorus absorption by the plants. Canavalia ensiformis displayed high potential for phytoextraction as these plants could translocate high copper concentrations to the aerial plant parts, while the Mucuna cinereum and M. aterrima are indicated for the copper phytostabilization programs, due to the high copper accumulation in their root systems.